Electric field distribution in 132 kV XLPE cable termination model from finite element method - Illias H.A.; Ng Q.L.; Bakar A.H.A.; Mokhlis H.; Ariffin A.M. (2023)
High voltage cable terminations are widely used in power system networks. A proper design of cable termination is essential in reducing the electric field distribution around the end of high voltage cable. However, if there are defects exist at cable termination structure, the electric field can be enhanced significantly and can be the source of electrical discharges. Therefore, it is important to understand the effect of defects on the electric field distribution at cable terminations. In this work, a 132 kV XLPE outdoor cable termination has been modelled using finite element analysis (FEA) method. The model has been used to simulate the electric field distribution in the cable termination in the presence of defects. Defects that have been considered are void defect in porcelain, stress cone and fluid, sharp pin on the porcelain surface and delamination defect between the insulator and the stress cone. The effect of different void location, material dielectric constant and porcelain radius on the electric field magnitude at cable termination have also been investigated. From the results obtained in this work, a better understanding of the electric field distribution at the cable termination with defects can be attained. 2012 IEEE.